The Effect of including dried citrus pulp and mulberry leaf powder in broiler feed on growth performance - علي, عمار; وليد الرحمون; توفيق دلا; علي نيصافي (Latakia University Journal -Biological Sciences Series, 2025)
The research was conducted to evaluating the effect of partially replacing corn and soybean meal in broiler mixtures with citrus pulp and mulberry leaf powder. The research was carried out on a private farm in the Baniyas region, and 120 chicks of the commercial hybrid ROSS were used in the experiment, distributed into four treatments. The first treatment (the control) was given a basic fodder mixture. The second , T1, used citrus pulp, the third, T2, mulberry leaf powder, and the fourth, T3, used a mixture of citrus pulp and mulberry leaf powder. At the end of the experiment at 42 days of age, the following productive indicators were studied: live body weight, feed intake, feed conversion ratio, and the Production guide. The results showed that the best live body weight was in the T1 treatment without significant differences (P>0.05) compared to the control, and it outperformed the T2 and T3 treatments with significant differences (P<0.05). As for the feed intake, no significant differences were observed between treatment T1 and the control and between treatments T2 and T3 and the control, while in treatments T2 and T3 it was higher and with significant differences compared to treatment T1 (P<0.05). The best value of the feed conversion ratio was for the control and treatment T1, without significant differences between them (P>0.05), while the value of the feed conversion ratio for treatments T2 and T3 was higher compared to the control, with significant differences (P<0.05). The highest value of the production guide was for treatment T1, without significant differences compared with the control (P>0.05). The results of the current study showed that dried citrus pulp can be used as a substitute for corn in broiler feed at a rate of 5% without any negative effect on growth performance.